2010
DOI: 10.1080/17450390903499915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dose and formulation of carvacrol and thymol on bacteria and some functional traits of the gut in piglets after weaning

Abstract: Two trials were conducted to study the effects of dose and formulation of carvacrol and thymol on bacterial counts, metabolites and functional traits of the gut in weaned piglets. In the first experiment (Exp. I), 25 piglets (28 d, 6.59 +/- 0.48 kg BW) were allocated to five dietary treatments: a control diet, or the same diet supplemented with either carvacrol or thymol at doses of 500 and 2000 mg kg(-1). In the second experiment (Exp. II), 35 piglets (28 d, 7.99 +/- 0.73 kg BW) were assigned to seven dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
75
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 31 publications
10
75
2
7
Order By: Relevance
“…In the current study feed choice is certainly driven by the feed flavour (short duration and daily alternating feeder position) in contrast to the 12-day duration of the other study where nutritional, metabolic and physiological factors may become relevant. However, in Michiels et al (2010) no such arguments were found that could explain the higher feed intake in the no choice-feeding situation. Perhaps, thymol's pungency stimulated digestive secretions and intestinal motility leading to shortening of digesta transit and increased feed consumption as was evidenced with several spices (Platel and Srinivasan, 2001).…”
Section: Penmentioning
confidence: 90%
See 3 more Smart Citations
“…In the current study feed choice is certainly driven by the feed flavour (short duration and daily alternating feeder position) in contrast to the 12-day duration of the other study where nutritional, metabolic and physiological factors may become relevant. However, in Michiels et al (2010) no such arguments were found that could explain the higher feed intake in the no choice-feeding situation. Perhaps, thymol's pungency stimulated digestive secretions and intestinal motility leading to shortening of digesta transit and increased feed consumption as was evidenced with several spices (Platel and Srinivasan, 2001).…”
Section: Penmentioning
confidence: 90%
“…The preference for feed containing 1250 mg/kg was 36.8% and thus intermediate with the results of trial A. In previous work (Michiels et al, 2010) the addition of 500 and 2000 mg/kg thymol to diets for freshly weaned piglets in a 12-day trial was investigated. Although the objective in that study was not to evaluate the effect on animal performances, the actual feed intake relative to the control diet was 123 and 99% for the treatments 500 and 2000 mg/kg thymol respectively.…”
Section: Penmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, as an alternative to the use of synthetic chemotherapeutics, several natural products based on aromatic plants have drawn great attention and have been studied in different species of zootechnical interest, such as fish (ABBAS et al, 2012;CHAVES et al, 2011;GIANNENAS et al, 2003;MICHIELS et al, 2010;ZHENG et al, 2009). The search for alternative additives with the potential to enhance zootechnical performance and improve the immune system of the animal without leaving any residue in the fish meat or resulting in resistant bacteria has driven research on the inclusion of natural products in fish diets (CAMPAGNOLO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%